2015
DOI: 10.1007/s13277-015-3085-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-511 inhibits growth and metastasis of human hepatocellular carcinoma cells by targeting PIK3R3

Abstract: MicroRNAs (miRNAs) are critical for cancer development and progression. Elucidating the underlying mechanism of miRNAs in carcinogenesis may lead to novel diagnostic and therapeutic strategies for malignancy. In this study, we found that miR-511 expression was markedly downregulated in hepatocellular carcinoma (HCC) cell lines and tissues. Phosphoinositide-3-kinase regulatory subunit 3 (PIK3R3) was identified as a direct target of miR-511 and miR-511 expression inversely correlated with PIK3R3 mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…lncRNA-PAGBC requires miR-133b and miR-511 to promote growth and metastasis and activate the AKT/mTOR pathway in GBC cells Fig S2, miR-133b and miR-511 could strongly inhibit the proliferation, colony formation and metastasis abilities of GBC cells. Both SOX4 and PIK3R3 have been shown to promote proliferation and metastasis in other carcinomas in previous studies [18][19][20][21]. Moreover, these studies demonstrated that both SOX4 and PIK3R3 are involved with the AKT/mTOR pathway, which is critical for tumour proliferation and metastasis.…”
Section: Lncrna-pagbc Upregulates Sox4 and Pik3r3 Levelsmentioning
confidence: 83%
See 1 more Smart Citation
“…lncRNA-PAGBC requires miR-133b and miR-511 to promote growth and metastasis and activate the AKT/mTOR pathway in GBC cells Fig S2, miR-133b and miR-511 could strongly inhibit the proliferation, colony formation and metastasis abilities of GBC cells. Both SOX4 and PIK3R3 have been shown to promote proliferation and metastasis in other carcinomas in previous studies [18][19][20][21]. Moreover, these studies demonstrated that both SOX4 and PIK3R3 are involved with the AKT/mTOR pathway, which is critical for tumour proliferation and metastasis.…”
Section: Lncrna-pagbc Upregulates Sox4 and Pik3r3 Levelsmentioning
confidence: 83%
“…Maybe it can also happen to lncRNAs when they work as ceRNAs in cytoplasm. Additionally, SOX4 and PIK3R3, which are target genes of these two miRNAs and have been identified as oncogenic genes in other malignancies [18][19][20][21], were found to be positively regulated by lncRNA-PAGBC. Again, as expected, this positive relationship was demonstrated to depend on the competitive role of two miRNAs, at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that miR-511 overexpression significantly decreased the expression of p-Akt, β-catenin, c-Myc and cyclinD1, suggesting that miR-511 acts as a negative regulator of these two pathways. Previous study also showed that miR-511 acts as a negative regulator of PI3K/AKT pathway in liver cancer [38]. Further findings showed overexpression of TRIM24 lacking its 3′-UTR significantly restored PI3K/AKT and Wnt/β-catenin pathways in miR-511-transfected GC cells.…”
Section: Discussionmentioning
confidence: 71%
“…Apoptosis induced by parquet was associated with decreased PIK3R3 expression and caspase activation [28]. Furthermore, PIK3R3 could promote cell migration and invasion in various types of cancer via different mechanisms [29], for example, this protein could enhance the migration and invasion of colorectal cancer by SLUG triggered EMT [19]. Similar to above-mentioned results, our data demonstrated that PIK3R3 could promote the migration and invasion of PC cells for the first time by experiments both in vitro and in vivo , and this function of PIK3R3 might be depending on the ZEB1 induced EMT.…”
Section: Discussionmentioning
confidence: 99%